Development of accurate force fields for the simulation of biomineralisation - Raiteri, Paolo; Demichelis, Raffaella; Gale, Julian (Academic Press, 2013)
The existence of an accurate force field model that reproduces the free energy landscape is a key pre-requisite for the simulation of biomineralisation. Here the stages in the development of such a model are discussed including the quality of the water model, the thermodynamics of polymorphism and the free energies of solvation for the relevant species. The reliability of force fields can then be benchmarked against quantities such as the free energy of ion pairing in solution, the solubility product, and the structure of the mineral-water interface.